Assessing muscular performance across the menstrual cycle in collegiate softball players - Houchlei, S. L.; Gillett, M. G.; Falk, A. P.; Chance, R. C.; Miller, S. K.; Wood, S. N.; Peters, S. E.; Martens, A. C.; Gordon, R. A. (International Journal of Exercise Science Conference Proceedings, 2025)
PURPOSE: The menstrual cycle is characterized by fluctuations in estrogen and progesterone that may impact training performance in females. We investigated whether there were differences in muscular performance measures throughout the menstrual cycle in NCAA D1 softball players. METHODS: D1 softball athletes participated in this study (n = 11; 19 ± 1 yr). The initial visit assessed height, weight, body composition (InBody 770), resting metabolic rate (Parvo TrueOne 2400), and cycle history using the FLO app. Other visits occurred during their projected early-follicular (EF), ovulatory (OV), and mid-luteal (ML) phases for performance testing. Each visit participants rated current perceived fatigue, motivation, strength, and energy. Following a standardized warm-up, a countermovement jump (CMJ) on a force plate (SPARTA) and 3, 15-yard sprints using timing gates (Vald Smart Speed) were performed. Velocity characteristics (Vitruve) were then assessed through 3 maximal-effort back squats at 70% of their 1RM. Differences in the data collected between EF, OV, and ML were determined using a one-way, repeated measures MANOVA followed by Bonferroni post-hoc testing. All data are reported as mean ± standard deviation, and a was set at p = .05. RESULTS: Maximal force (8.2% > OV, 7.6% > EF; N/kg), power (12.1% > OV, 12.5% > EF; W/kg), jump height (5.3% > OV, 6.2% > EF; m), and maximal velocity (2.6% > OV, 3.4% > EF; m/s) during the CMJ peaked during ML, though there was no significance (p > .05). Time to max acceleration (4.1% > ML, 9.0% > EF; s), time to take-off (6.7% > ML, 9.3% > EF; s), and sprint time (2% > ML and EF; s) peaked during OV, though there was no significance (p > .05). Squat velocity (3.1% > OV, 1.5% > ML; m/s) peaked during EF, though there was no significance (p > .05). CONCLUSION: Performance variables from a CMJ test were maximized during ML and OV, while squat velocity was maximized during EF. No statistical significance was observed. Further data collection will clarify the potential differences in these performance characteristics in female athletes throughout the menstrual cycle.